2004
DOI: 10.1103/physrevlett.93.201301
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Baryogenesis

Abstract: We show that a gravitational interaction between the derivative of the Ricci scalar curvature and the baryon-number current dynamically breaks CPT in an expanding Universe and, combined with baryon-number-violating interactions, can drive the Universe towards an equilibrium baryon asymmetry that is observationally acceptable.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
474
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(478 citation statements)
references
References 25 publications
4
474
0
Order By: Relevance
“…At this point it is worth noticing that, although in four-dimensional gravity it is natural to expect M * of the order of the Planck mass M 4 , this may not be necessarily the case. For instance, M * ≃ (M R M 4 ) 1/2 could be possible, if the right-handed neutrino Majorana mass M R softly violates baryon number [5]. Moreover, this scale can be much lower, if the effective four-dimensional theory comes from a higher-dimensional theory.…”
Section: Gravitational Leptogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…At this point it is worth noticing that, although in four-dimensional gravity it is natural to expect M * of the order of the Planck mass M 4 , this may not be necessarily the case. For instance, M * ≃ (M R M 4 ) 1/2 could be possible, if the right-handed neutrino Majorana mass M R softly violates baryon number [5]. Moreover, this scale can be much lower, if the effective four-dimensional theory comes from a higher-dimensional theory.…”
Section: Gravitational Leptogenesismentioning
confidence: 99%
“…The framework presented here is based on the CP T -violating gravitational interaction between the derivative of the Ricci scalar curvature and the B (or B − L) current [5]. We have shown that it is possible to generate the correct magnitude of the baryon asymmetry in different cosmological scenarios, depending on whether the decoupling of the B-or (B − L)-violating interactions occurs in standard cosmology or in the high-energy Randall-Sundrum or Gauss-Bonnet braneworld regimes.…”
Section: Gravitational Leptogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The gravitational baryogenesis (GB) process was proposed in 2004 by Davoudiasl et al [14], in order to explain the observed imbalance of matter over antimatter in the observable universe. The cosmic microwave background observations [15] and also the Big Bang nucleosynthesis [16] admit this imbalance of matter (baryons) and antimatter (antibaryons).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we try to consider the GB process in the context of DGP brane cosmology, and the goal of the present paper is to highlight the differences of the GB process between the DGP brane cosmology and standard cosmology. However, the imbalance of the matter and antimatter GB term is given by [14] 1…”
Section: Introductionmentioning
confidence: 99%